Pendidikan Multikultural Dalam Ekstrakurikuler PramukaUntuk Memperkuat Wawasan Kebangsaan Pada Siswa KelasVII SMP Negeri 1 Boyolali Tahun Pelajaran 2015/2016 - Fatmala, Kiki, Drs. Yulianto Bambang Setyadi, M.Si (2016)
This study aimed to describe the multicultural education in extracurricular scout to strengthen national awareness in students of class VII in SMP Negeri 1 Boyolali in the academic year 2015/2016. This type of research is a case study because it focuses on a specific case. Data collection techniques in this study using the method of observation, interviews, and documentation. This study uses triangulation triangulation of data sources and data collection techniques. The data analysis applying interactive models through data collection, data reduction, data presentation, and conclusion. The results of this study show that: 1) multicultural education conducted in scout activities such as the opening ceremony, marching regulations (UN), campsite, semapore, Morse, passwords, browsing, and entertainment. Such activities can form the characters of learners such as equality, justice, mutual respect, mutual tolerance, and pluralism; 2) obstacles in implementing multicultural education in extracurricular scout is still their students' individual, yet can implement multicultural education in society; 3) solution in dealing with the implementation of multicultural education in extracurricular scouts that the builder gave an example through attitude and provide a better understanding of diversity that exist in Indonesia.